FEASIBILITY OF SOYBEAN FARMING BUSINESS FROM YOUTH AND OLD SUBSIDIARIES OF GROBOGAN LOCAL VARIETIES - Febyningsi Rambu Ladu Mbana; Tinjung Mary Prihtanti; Yuliawati Yuliawati (Faculty of Animal and Agricultural Science, Diponegoro University, 2021)
The demand for soybean needs continues to increase every year. This is not matched by productivity. The role of the government is to attract farmers to conduct business by providing subsidies. Even though they haven't reached the productivity target, some farmers conduct the early harvest. Therefore, this study aims to: 1) determine the R/C ratio of young soybean pods and old soybean pods commodity, knowing the breakeven point of productivity and prices of young soybean pods and old pods. The location selection was carried out purposively (purposive) and the determination of respondents using purposive sampling technique with a total of 39 respondents. Data sources used secondary and primary data. The data collection method was conducted by interview. This research used R/C ratio analysis, breakeven analysis of productivity and price. The results showed that the R/C ratio of commodity young soybean pods> 1.23, old pods = 1. The breakeven point of productivity and price of young pods was 523 kg/ha, IDR 763 kg and old pods 708.21 kg/ha, IDR 1,214, 93 kg, this exceeds the breakeven point of productivity and price and thus results in a profit. Therefore, there is a need for the government to play a role in setting prices for old soybean pods to attract farmers to cultivate old soybean pods.